(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2021)
Psychological Autopsy (PA) is a retrospective analysis in the case of equivocal death. Equivocal death is defined as a death that is unknown, undetermined, ambiguous. Specifically considering the case of suicide, many times the exact manner of death is undetermined (i.e. factor which instigated the person to commit suicide). Psychological Autopsy is an approach to scrutinize the risk factor and the psychological state of an individual prior to death. This whole process is carried on by collecting all relevant documents (medical reports, coroner report, details of death, personal documents) of the deceased and extensive interview of family members, friends, next of kin, all people related to the case is interrogated. Finally, after psychoanalysis of the deceased, the manner of death is concluded by synthesizing all collected data. To determine whether it is a case of suicide, abetment to suicide, or accident. This paper reviews the aspect of Psychological Analysis (PA) needed in every suicide case along with the post-mortem examination to determine the root cause of committing suicide.